2023
DOI: 10.3390/sports11080141
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Dynamic Forces and Kinematic Indicators of Front and Roundhouse Kicks across Varied Conditions and Participant Experience

Abstract: Impact force and maximum velocity are important indicators of kick efficiency. Therefore, this systematic review compared the front kick (FK) and roundhouse kick (RK), including their impact force, maximum velocity, angular velocity, and execution time, considering various target types and experience levels. Following PRISMA guidelines, the Web of Science, SportDiscus, and PubMed were systematically searched for articles published from January 1982 to May 2022. Normalized kicking values were compared using one… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Unfortunately, there are not many studies recording the force of kicks in taekwon-do. In the review of Vagner et al [33], the reported values of roundhouse kicks were much lower, ranging from 1200-1800 N. A study by Thibordeeand and Prasartwuth [34] had even lower values of up to 200 N. A study of side kicks by Lee et al [35] also obtained lower values of around 1300 N. Differences in the study designs can be attributed to various factors, such as the chosen targets, their size, the distance of participants from these targets, and the height of the targets. These elements must be considered when comparing force values across different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are not many studies recording the force of kicks in taekwon-do. In the review of Vagner et al [33], the reported values of roundhouse kicks were much lower, ranging from 1200-1800 N. A study by Thibordeeand and Prasartwuth [34] had even lower values of up to 200 N. A study of side kicks by Lee et al [35] also obtained lower values of around 1300 N. Differences in the study designs can be attributed to various factors, such as the chosen targets, their size, the distance of participants from these targets, and the height of the targets. These elements must be considered when comparing force values across different studies.…”
Section: Discussionmentioning
confidence: 99%
“…In combat sports, this principle suggests the relationship between the mass and the dynamic forces of the strike. Therefore, previous studies have explored the dynamic forces of punches and kicks [24][25][26][27][28][29][30]. Additionally, some studies have demonstrated that dynamic forces like peak or impact force within the kicks partially depend on a subject's mass [6][7][8]31].…”
Section: Introductionmentioning
confidence: 99%